Method for preparing low-alkali high-purity silicon-aluminum micro-powder from lithium slag
Patent Information
- Application Number
- CN202610841938.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-11
- Publication Date
- 2026-08-18
AI Technical Summary
然而,这些方法均采用碱浸出等化学湿法工艺,虽然能够实现碱金属的脱除,但存在工艺复杂、处理成本高、易产生二次废液等问题
[0035] 1. This invention utilizes a multi-stage combined process of "desulfurization-gradation-potassium and sodium removal-iron removal" to deeply remove harmful impurities from lithium slag. The resulting low-alkali, high-purity silicon-aluminum micropowder has extremely low alkali metal oxide content (Na2O + K2O < 0.5%, Li2O < 0.2%), while the content of impurities such as sulfur and iron is also strictly controlled (SO3 < 0.4%, Fe2O3 < 0.4%). The product has high purity and stable quality, meeting the production requirements of electronic-grade alkali-free glass fiber and effectively replacing natural mineral resources such as pyrophyllite. Furthermore, the yield of the silicon-aluminum micropowder product is significantly improved, a result we did not expect.
Smart Images

Figure CN122586060A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing low-alkali, high-purity silicon-aluminum micro powder from lithium slag, belonging to the field of solid waste recycling technology. Background Technology
[0002] Glass fiber (GF), as a high-performance inorganic non-metallic material, possesses characteristics such as high temperature resistance, non-combustibility, corrosion resistance, good thermal and sound insulation, and high tensile strength. It is commonly used as a reinforcing material, electrical insulation material, and thermal insulation material in composite materials, and is widely applied in key fields such as construction, transportation, electronics, industrial equipment, and new energy. In recent years, the glass fiber industry has been experiencing a new round of rapid growth. Especially driven by high-end applications such as lightweight wind turbine blades, 5G base station construction, new energy vehicles, and electronic-grade copper clad laminates (CCL), the market has placed more stringent demands on the performance of glass fiber products. With the popularization of intelligent technologies such as AI and autonomous driving, the market demand for special electronic cloths with low dielectric constant and high stability continues to rise. However, the preparation of high-end glass fiber products has extremely strict limitations on the chemical composition of raw materials, which directly affects the stability of the melting process, the quality of fiber forming, and the electrical properties of the final product.
[0003] Meanwhile, with the rapid development of the new energy industry, global demand for lithium salts is growing rapidly. Existing lithium ore extraction processes (such as spodumene and lepidolite) generate a large amount of lithium slag annually. The main chemical components of lithium slag are typically silicon dioxide (SiO2) and aluminum oxide (Al2O3), which can account for up to 80% of the total composition. It also contains small amounts of impurities such as calcium, magnesium, iron, and alkali metals (potassium and sodium). From a resource recycling perspective, lithium slag is a potentially high-quality raw material for preparing high-value-added materials such as silica-alumina micropowder, geopolymers, and zeolite molecular sieves. Purifying the silica-alumina components in lithium slag and preparing silica-alumina micropowder can replace natural minerals such as pyrophyllite and kaolin as a source of siliceous and aluminous raw materials for glass fiber production. This not only achieves high-value transformation of industrial solid waste but also effectively reduces the glass fiber industry's dependence on natural minerals.
[0004] However, the core obstacle limiting the application of lithium slag-based silica-alumina micropowder in the glass fiber field lies in its high alkali metal content (mainly K2O and Na2O). During the glass fiber melting process, while alkali metal oxides (R2O) can act as fluxes to reduce the viscosity of the molten glass, excessively high potassium and sodium content significantly lowers the crystallization temperature of the molten glass, leading to crystallization during fiber drawing, causing wire breakage, strand breakage, and even production interruption, severely impacting operational stability and yield. More importantly, for high-end products such as electronic-grade glass fiber, alkali metal ions have strong migration capabilities under humid and hot environments or electric fields, significantly reducing the resistivity of the glass fiber and deteriorating its dielectric properties. This makes it impossible to meet the stringent requirements of low dielectric constant and low dielectric loss for copper-clad laminates in high-frequency, high-speed transmission scenarios. According to relevant industry technical specifications, the raw materials used for electronic-grade glass fiber have extremely strict limits on the total amount of alkali metal oxides, typically requiring an alkali metal oxide content of less than 0.8%.
[0005] However, due to the characteristics of the lithium extraction process, the raw materials inherently contain high levels of potassium and sodium, making it difficult to effectively remove the residual potassium and sodium from the resulting lithium slag through simple physical washing or traditional processes. Directly preparing these high-potassium, high-sodium lithium slags into silicon-aluminum micropowders and using them as fiberglass feedstock would result in serious defects in the electrical insulation, chemical stability, and molding processability of the fiberglass products, failing to meet the entry standards of downstream markets, especially in the electronics and electrical appliance sector.
[0006] Patent CN 118792502 A discloses a method for efficient lithium extraction from spodumene clinker and the preparation of low-iron, low-sulfur silicon-aluminum micropowder. While preparing the low-iron, low-sulfur silicon-aluminum micropowder, the product contains Na₂O+K₂O between 0.4% and 0.6%. Although the potassium and sodium content is low, this method differs from current market spodumene smelting processes. Furthermore, the low Na₂O+K₂O content in the spodumene raw material used makes it unsuitable for large-scale lithium slag production. Patent CN 117165787 B provides a method for lithium extraction from spodumene while simultaneously recovering low-iron, low-sulfur silicon-aluminum micropowder, high-purity gypsum, tantalum-niobium concentrate, and lithium-rich iron. The silicon-aluminum micropowder prepared by this method contains Na₂O+K₂O between 0.7% and 0.8%, which is relatively high and does not meet the raw material standards for the glass fiber industry.
[0007] Furthermore, existing technologies also include methods specifically designed for removing alkali metals from lithium slag. For example, patent CN119638237A discloses a method for removing potassium and sodium from lithium slag, and patent CN119876610A discloses a method for extracting potassium, sodium, rubidium, and cesium from lithium slag. However, these methods all employ chemical wet processes such as alkaline leaching. While they can remove alkali metals, they suffer from complex processes, high processing costs, and the potential for generating secondary waste liquid. In particular, none of these methods provide a systematic solution that can be integrated with desulfurization and iron removal processes to achieve comprehensive utilization of all components of lithium slag while economically and efficiently producing low-alkali, high-purity silica-alumina micropowder.
[0008] How to extract valuable silicon and aluminum components from lithium slag while simultaneously removing potassium and sodium impurities using economical and environmentally friendly physical or physicochemical methods, and producing low-alkali, high-purity silicon and aluminum micro powder with a total alkali content (K2O+Na2O) of less than 0.5% and qualified sulfur and iron content, has become a key technical challenge that urgently needs to be solved in the field of high-value utilization of lithium slag resources. Summary of the Invention
[0009] The first objective of this invention is to provide a method for preparing low-alkali, high-purity silicon-aluminum micropowder from lithium slag.
[0010] To achieve the first objective of this invention, the lithium slag is a solid waste residue obtained after lithium extraction from lithium-containing minerals via acid extraction, neutralization, and filtration. The method includes the following steps:
[0011] a. Desulfurization: Lithium slag is pulped and desulfurized to obtain gypsum slag and desulfurized lithium slag. The gypsum slag is dehydrated to obtain gypsum powder.
[0012] b. Grading: The desulfurized lithium slag from step a is graded to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag. The coarse-grained desulfurized lithium slag contains less than 10% -325 mesh, and the fine-grained desulfurized lithium slag contains more than 95% -325 mesh.
[0013] c. Removal of potassium, sodium, and iron: The coarse-grained desulfurized lithium slag from step b is subjected to potassium and sodium removal treatment to obtain alkali-rich slag and low-alkali desulfurized lithium slag. The low-alkali desulfurized lithium slag is then subjected to iron removal treatment to obtain low-alkali silica-alumina powder and iron-rich slurry 1. The alkali-rich slag is dewatered to obtain feldspar concentrate. The fine-grained desulfurized lithium slag from step b is subjected to iron removal treatment to obtain iron-rich slurry 2 and fine-grained silica-alumina powder. Iron-rich slurry 1 and iron-rich slurry 2 are combined to obtain iron-rich slurry. The iron-rich slurry is dewatered to obtain iron-rich material.
[0014] d. Grinding and mixing: Grind the low-alkali silicon-aluminum powder from step c to obtain low-alkali silicon-aluminum micro powder. Then mix the low-alkali silicon-aluminum micro powder with the fine-particle silicon-aluminum powder from step c, and dehydrate to obtain low-alkali high-purity silicon-aluminum micro powder.
[0015] Alternatively, the low-alkali silicon-aluminum powder from step c can be mixed with fine-grained silicon-aluminum powder, ground, and then dehydrated to obtain low-alkali, high-purity silicon-aluminum micro powder.
[0016] For lithium slag prepared by the sulfuric acid process, this invention extracts valuable silicon and aluminum components while deeply removing potassium and sodium impurities, thus preparing low-alkali, high-purity silicon and aluminum micro powder that meets the raw material standards of the high-end glass fiber industry.
[0017] The "grading" step described in this invention is not a closed-circuit grinding stage set up solely to control grinding fineness in traditional processes. Instead, it is mainly based on the inventors' discovery of specific segregation and enrichment patterns of potassium and sodium minerals in lithium slag. A multi-stage combined process of "desulfurization-grading-potassium and sodium removal-iron removal" is proposed. By grading the desulfurized lithium slag, potassium and sodium are specifically removed from the coarse particles, and iron is removed from both the coarse and fine particles, thereby achieving the dual goals of deep dealkali removal and efficient iron removal.
[0018] The lithium-containing minerals are lithium-containing minerals found in nature, such as spodumene and petalite.
[0019] In one specific embodiment, in step a, the lithium slag particle size is -200 mesh, accounting for 50-80 wt%; the pulp concentration is preferably 20-50%; and the desulfurization treatment preferably includes at least one of flotation and acid dissolution. The flotation reagent used during desulfurization is a conventional desulfurization flotation reagent.
[0020] In one specific embodiment, the gypsum slag obtained in step a contains SO3 ≥ 42%, and the desulfurized lithium slag contains SO3 ≤ 0.5%.
[0021] In one specific embodiment, step b, the grading process includes at least one of screening grading, hydrocyclone grading, and spiral grading.
[0022] In one specific embodiment, in step c, the removal of potassium sodium is carried out by flotation, and the flotation for removing potassium sodium includes at least one of a modifier, a depressant, an activator, and a collector; the dosage of the modifier is 500-2000 g / t, the dosage of the depressant is 100-1000 g / t, the dosage of the activator is 50-300 g / t, and the dosage of the collector is 100-1000 g / t; the modifier for removing potassium sodium includes at least one of sulfuric acid, sodium hydroxide, sodium carbonate, and oxalic acid; the depressant includes at least one of water glass, sodium silicate, sodium hexametaphosphate, starch, carboxymethyl cellulose, and citric acid; the activator includes at least one of sodium fluorosilicate, sodium fluoride, sodium dodecyl sulfate, ammonium dodecyl sulfate, ethylenediamine phosphate, and sodium diethylamine phosphate; and the collector includes at least one of dodecylamine, oleic acid, sodium oleate, sodium dodecyl sulfonate, sodium petroleum sulfonate, octyl hydroxamic acid, and dodecyl trimethylammonium chloride; the removal of iron preferably includes at least one of magnetic separation or gravity separation.
[0023] In one specific embodiment, in step c, the Na2O+K2O content in the rich alkali slag is ≥9.0%, and the Na2O+K2O content in the low alkali desulfurization lithium slag is ≤0.5%.
[0024] In one specific embodiment, in step c, the Fe2O3 content in the fine-grained silicon-aluminum powder is ≤0.4%, the Fe2O3 content in the low-alkali silicon-aluminum powder is ≤0.4%, and the Fe2O3 content in the iron-rich material is ≥4.0%.
[0025] In one specific embodiment, in step d, the fineness of the obtained low-alkali silica-alumina micro powder is -325 mesh with a content ≥95%.
[0026] In one specific embodiment, step d includes at least one of ball milling and rod milling; the milling time is preferably 10-30 minutes, and the slurry concentration is preferably 40-60%.
[0027] The grinding process is preferably performed using a ceramic ball mill.
[0028] In one specific embodiment, the dehydration process includes at least one of concentration, filtration, and drying; preferably, the dehydration is carried out until the moisture content of the product is ≤2.0%, more preferably 1.0%.
[0029] In one specific embodiment, the obtained low-alkali high-purity silicon-aluminum micro powder contains Na2O+ K2O < 0.5%, Li2O ≤ 0.2%, SO3 < 0.40%, and Fe2O3 < 0.40%; preferably, Na2O+ K2O < 0.40%.
[0030] In one specific embodiment, the lithium slag contains 50%–65% SiO2, 15%–25% Al2O3, 3%–8% SO3, 0.3%–1.5% K2O, 0.2%–1.0% Na2O, 0.8%–1.5% Fe2O3, and 0.2%–0.5% Li2O.
[0031] In one specific embodiment, the gypsum powder is used to prepare gypsum board, gypsum blocks, or cement retarder; the feldspar concentrate is used as a ceramic raw material; the low-alkali, high-purity silica-alumina micro powder is used to replace pyrophyllite in the preparation of alkali-free glass fiber; and the iron-rich material is further used for sorting to obtain at least one of lithium concentrate, iron material, tantalum-niobium concentrate, or tin concentrate.
[0032] The second objective of this invention is to provide a low-alkali, high-purity silicon-aluminum micro powder.
[0033] To achieve the second objective of this invention, the low-alkali, high-purity silicon-aluminum micro powder is prepared by the method described above.
[0034] Beneficial effects:
[0035] 1. This invention utilizes a multi-stage combined process of "desulfurization-gradation-potassium and sodium removal-iron removal" to deeply remove harmful impurities from lithium slag. The resulting low-alkali, high-purity silicon-aluminum micropowder has extremely low alkali metal oxide content (Na2O + K2O < 0.5%, Li2O < 0.2%), while the content of impurities such as sulfur and iron is also strictly controlled (SO3 < 0.4%, Fe2O3 < 0.4%). The product has high purity and stable quality, meeting the production requirements of electronic-grade alkali-free glass fiber and effectively replacing natural mineral resources such as pyrophyllite. Furthermore, the yield of the silicon-aluminum micropowder product is significantly improved, a result we did not expect.
[0036] 2. This invention not only focuses on the preparation of the target product, silicon-aluminum micro powder, but also transforms the sulfur, alkali metals, iron, and other components in lithium slag into valuable by-products. Through the ingenious design of the process route, gypsum powder (for building materials), feldspar concentrate (for ceramics), and iron-rich material (for further recovery of valuable metals) are obtained, realizing the full-component resource utilization of industrial solid waste, completely solving the environmental pressure caused by lithium slag stockpiling, and achieving the goal of zero emissions.
[0037] 3. Based on the newly discovered specific segregation and enrichment patterns of potassium and sodium minerals in lithium slag, this invention performs "grading treatment" before impurity removal, dividing the desulfurized lithium slag into coarse and fine particles according to particle size and treating them separately, which is highly efficient and economical.
[0038] 4. This method, through a combination of physicochemical methods such as flotation and magnetic separation, effectively addresses the complex composition and diverse impurities of lithium extraction tailings from the sulfuric acid process. The final products can be sold as industrial raw materials, creating new profit growth points for enterprises while mitigating environmental protection investments. The entire process is simple, easy to industrialize, highly adaptable, and offers significant economic benefits. Attached Figure Description
[0039] Figure 1 This is a process flow diagram for preparing low-alkali, high-purity silicon-aluminum micropowder from lithium slag according to the present invention.
[0040] Figure 2 This is a process flow diagram for Comparative Example 1 (traditional process).
[0041] Figure 3 This is the process flow diagram for Comparative Example 2 (non-grading treatment).
[0042] Figure 4 This is the process flow diagram for Comparative Example 3 (non-grading magnetic separation process).
[0043] Figure 5 This is a process flow diagram for Comparative Example 4 (magnetic separation followed by grading process). Detailed Implementation
[0044] To achieve the first objective of this invention, the lithium slag is a solid waste residue obtained after lithium extraction from lithium-containing minerals via acid extraction, neutralization, and filtration. The method includes the following steps:
[0045] a. Desulfurization: Lithium slag is pulped and desulfurized to obtain gypsum slag and desulfurized lithium slag. The gypsum slag is dehydrated to obtain gypsum powder.
[0046] b. Grading: The desulfurized lithium slag from step a is graded to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag. The coarse-grained desulfurized lithium slag contains less than 10% -325 mesh, and the fine-grained desulfurized lithium slag contains more than 95% -325 mesh.
[0047] c. Removal of potassium, sodium, and iron: The coarse-grained desulfurized lithium slag from step b is subjected to potassium and sodium removal treatment to obtain alkali-rich slag and low-alkali desulfurized lithium slag. The low-alkali desulfurized lithium slag is then subjected to iron removal treatment to obtain low-alkali silica-alumina powder and iron-rich slurry 1. The alkali-rich slag is dewatered to obtain feldspar concentrate. The fine-grained desulfurized lithium slag from step b is subjected to iron removal treatment to obtain iron-rich slurry 2 and fine-grained silica-alumina powder. Iron-rich slurry 1 and iron-rich slurry 2 are combined to obtain iron-rich slurry. The iron-rich slurry is dewatered to obtain iron-rich material.
[0048] d. Grinding and mixing: Grind the low-alkali silicon-aluminum powder from step c to obtain low-alkali silicon-aluminum micro powder. Then mix the low-alkali silicon-aluminum micro powder with the fine-particle silicon-aluminum powder from step c, and dehydrate to obtain low-alkali high-purity silicon-aluminum micro powder.
[0049] Alternatively, the low-alkali silicon-aluminum powder from step c can be mixed with fine-grained silicon-aluminum powder, ground, and then dehydrated to obtain low-alkali, high-purity silicon-aluminum micro powder.
[0050] For lithium slag produced by the sulfuric acid lithium extraction process, how can we extract valuable silicon and aluminum components while deeply removing potassium and sodium impurities to prepare low-alkali, high-purity silicon and aluminum micropowder that meets the raw material standards of the high-end glass fiber industry?
[0051] The "grading" step described in this invention is not a closed-circuit grinding stage set up solely to control grinding fineness in traditional processes. Instead, it is mainly based on the inventors' discovery of specific segregation and enrichment patterns of potassium and sodium minerals in lithium slag. A multi-stage combined process of "desulfurization-grading-potassium and sodium removal-iron removal" is proposed. By grading the desulfurized lithium slag, potassium and sodium are specifically removed from the coarse particles, and iron is removed from both the coarse and fine particles, thereby achieving the dual goals of deep dealkali removal and efficient iron removal.
[0052] The lithium-containing minerals are lithium-containing minerals found in nature, such as spodumene and petalite.
[0053] In one specific embodiment, in step a, the lithium slag particle size is -200 mesh, accounting for 50-80 wt%; the pulp concentration is preferably 20-50%; and the desulfurization treatment preferably includes at least one of flotation and acid dissolution. The flotation reagent used during desulfurization is a conventional desulfurization flotation reagent.
[0054] In one specific embodiment, the gypsum slag obtained in step a contains SO3 ≥ 42%, and the desulfurized lithium slag contains SO3 ≤ 0.5%.
[0055] In one specific embodiment, step b, the grading process includes at least one of screening grading, hydrocyclone grading, and spiral grading.
[0056] In one specific embodiment, in step c, the removal of potassium sodium is carried out by flotation, and the flotation for removing potassium sodium includes at least one of a modifier, a depressant, an activator, and a collector; the dosage of the modifier is 500-2000 g / t, the dosage of the depressant is 100-1000 g / t, the dosage of the activator is 50-300 g / t, and the dosage of the collector is 100-1000 g / t; the modifier for removing potassium sodium includes at least one of sulfuric acid, sodium hydroxide, sodium carbonate, and oxalic acid; the depressant includes at least one of water glass, sodium silicate, sodium hexametaphosphate, starch, carboxymethyl cellulose, and citric acid; the activator includes at least one of sodium fluorosilicate, sodium fluoride, sodium dodecyl sulfate, ammonium dodecyl sulfate, ethylenediamine phosphate, and sodium diethylamine phosphate; and the collector includes at least one of dodecylamine, oleic acid, sodium oleate, sodium dodecyl sulfonate, sodium petroleum sulfonate, octyl hydroxamic acid, and dodecyl trimethylammonium chloride; the removal of iron preferably includes at least one of magnetic separation or gravity separation.
[0057] In one specific embodiment, in step c, the Na2O+K2O content in the rich alkali slag is ≥9.0%, and the Na2O+K2O content in the low alkali desulfurization lithium slag is ≤0.5%.
[0058] In one specific embodiment, in step c, the Fe2O3 content in the fine-grained silicon-aluminum powder is ≤0.4%, the Fe2O3 content in the low-alkali silicon-aluminum powder is ≤0.4%, and the Fe2O3 content in the iron-rich material is ≥4.0%.
[0059] In one specific embodiment, in step d, the fineness of the obtained low-alkali silica-alumina micro powder is -325 mesh with a content ≥95%.
[0060] In one specific embodiment, step d includes at least one of ball milling and rod milling; the milling time is preferably 10-30 minutes, and the slurry concentration is preferably 40-60%.
[0061] The grinding process is preferably performed using a ceramic ball mill.
[0062] In one specific embodiment, the dehydration process includes at least one of concentration, filtration, and drying; preferably, the dehydration is carried out until the moisture content of the product is ≤2.0%, more preferably 1.0%.
[0063] In one specific embodiment, the obtained low-alkali high-purity silicon-aluminum micro powder contains Na2O+ K2O < 0.5%, Li2O ≤ 0.2%, SO3 < 0.40%, and Fe2O3 < 0.40%; preferably, Na2O+ K2O < 0.40%.
[0064] In one specific embodiment, the lithium slag contains 50%–65% SiO2, 15%–25% Al2O3, 3%–8% SO3, 0.3%–1.5% K2O, 0.2%–1.0% Na2O, 0.8%–1.5% Fe2O3, and 0.2%–0.5% Li2O.
[0065] In one specific embodiment, the gypsum powder is used to prepare gypsum board, gypsum blocks, or cement retarder; the feldspar concentrate is used as a ceramic raw material; the low-alkali, high-purity silica-alumina micro powder is used to replace pyrophyllite in the preparation of alkali-free glass fiber; and the iron-rich material is further used for sorting to obtain at least one of lithium concentrate, iron material, tantalum-niobium concentrate, or tin concentrate.
[0066] To achieve the second objective of this invention, the low-alkali, high-purity silicon-aluminum micro powder is prepared by the method described above.
[0067] The specific embodiments of the present invention will be further described below with reference to examples, but the present invention is not limited to the scope of the embodiments described herein.
[0068] Example 1
[0069] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0070] S1: Take 1000g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add the desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation, to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.37%; the lithium slag is the tailings obtained after lithium extraction from spodumene using the sulfuric acid method, and the chemical composition analysis results of the lithium slag are shown in Table 1.
[0071] Table 1. Multi-element chemical analysis of lithium slag
[0072]
[0073] Note: Given the low tantalum and niobium content in lithium slag, the test results of different batches of lithium slag may fluctuate, and the results of the same lithium slag sample may also fluctuate based on different test methods. This fluctuation is normal. The results of Nb2O5 and Ta2O5 in Table 1 are the average values of three parallel measurements of the same sample.
[0074] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 325-mesh square hole sieve to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag.
[0075] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 800g / t of sulfuric acid, 300g / t of carboxymethyl cellulose, 100g / t of sodium fluorosilicate, and 200g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0076] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0077] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0078] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 20 min, the slurry concentration is 50%, and the fineness is -325 mesh (98%).
[0079] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0080] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.93%, 0.62%, 0.68%, and 0.51%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0081] Example 2
[0082] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0083] S1: Take 1200g of lithium slag, with 68% of the lithium slag containing -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 35%, and then perform flotation operations sequentially using desulfurization flotation modifier, collector and frother to obtain gypsum slag and desulfurized lithium slag. The SO3 content in the desulfurized lithium slag is 0.39%.
[0084] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 325-mesh square hole sieve to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag.
[0085] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 500g / t of sodium hydroxide, 400g / t of water glass, 600g / t of sodium oleate and 200g / t of sodium dodecyl sulfonate as collectors for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0086] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry 2 and fine-grained silica-alumina powder.
[0087] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0088] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 20 minutes, the slurry concentration is 50%, and the fineness is -325 mesh (98%).
[0089] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0090] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.89%, 0.66%, 0.73%, and 0.56%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0091] Example 3
[0092] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0093] S1: Take 800g of lithium slag, with 60% of the lithium slag containing -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 25%, and then add the desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag. The SO3 content in the desulfurized lithium slag is 0.38%.
[0094] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 325-mesh square hole sieve to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag.
[0095] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 100g / t of sulfuric acid, 200g / t of carboxymethyl cellulose, 150g / t of sodium fluorosilicate, and 150g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0096] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0097] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0098] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 20 min, the slurry concentration is 50%, and the fineness is -325 mesh (98%).
[0099] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0100] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.84%, 0.58%, 0.62%, and 0.48%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0101] Example 4
[0102] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0103] S1: Take 1000g of lithium slag, with 78% of the lithium slag containing -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add the desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag. The SO3 content in the desulfurized lithium slag is 0.39%.
[0104] S2: The above-mentioned desulfurized lithium slag is classified using a hydrocyclone to obtain coarse-grained and fine-grained desulfurized lithium slag. Among them, the fine-grained desulfurized lithium slag contains 97% -325 mesh, and the coarse-grained desulfurized lithium slag contains 11% -325 mesh.
[0105] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 1000g / t of sulfuric acid, 500g / t of water glass, 100g / t of sodium fluorosilicate, and 150g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0106] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0107] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0108] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 20 min, the slurry concentration is 50%, and the fineness is -325 mesh (98%).
[0109] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0110] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.87%, 0.64%, 0.61%, and 0.55%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0111] Example 5
[0112] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0113] S1: Take 1000g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.39%.
[0114] S2: The above-mentioned desulfurized lithium slag is classified using a spiral classifier to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag. Among them, the fine-grained desulfurized lithium slag contains 96% -325 mesh, and the coarse-grained desulfurized lithium slag contains 17% -325 mesh.
[0115] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 1000g / t of sulfuric acid, 150g / t of sodium hexametaphosphate, 100g / t of sodium fluorosilicate, and 150g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0116] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0117] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0118] S6: The low-alkali silicon-aluminum powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silicon-aluminum micro powder; the grinding time is 20 minutes, the slurry concentration is 50%, and the fineness is -325 mesh (98%).
[0119] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0120] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 1.24%, 0.69%, 0.72%, and 0.58%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0121] Example 6
[0122] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0123] S1: Take 1000g of lithium slag, with 75% of the lithium slag containing -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add the desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag, with SO3 content of 0.40% in the desulfurized lithium slag.
[0124] S2: The above-mentioned desulfurized lithium slag is classified using a hydrocyclone to obtain coarse-grained and fine-grained desulfurized lithium slag. Among them, the fine-grained desulfurized lithium slag contains 99% -325 mesh, and the coarse-grained desulfurized lithium slag contains 23% -325 mesh.
[0125] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 1000g / t of sulfuric acid, 200g / t of carboxymethyl cellulose, 150g / t of sodium fluorosilicate, and 200g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0126] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.6T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0127] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0128] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 10 min, the slurry concentration is 60%, and the fineness is -325 mesh, accounting for 96%.
[0129] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0130] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.87%, 0.56%, 0.63%, and 0.48%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0131] Example 7
[0132] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0133] S1: Take 1000g of lithium slag, with 65% of the lithium slag containing -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add the desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag. The SO3 content in the desulfurized lithium slag is 0.38%.
[0134] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 300-mesh square-hole sieve to obtain coarse-grained and fine-grained desulfurized lithium slag. Among them, the fine-grained desulfurized lithium slag contains 99% -325 mesh.
[0135] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 28%, and then add 800g / t of sulfuric acid, 200g / t of carboxymethyl cellulose, 100g / t of sodium fluorosilicate, and 120g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0136] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.3T) and a high gradient strength separator (magnetic field strength 1.3T) to obtain iron-rich slurry 1 and fine-grained silicon-aluminum powder.
[0137] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.0T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder.
[0138] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 10 min, the slurry concentration is 45%, and the fineness is -325 mesh, accounting for 96%.
[0139] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0140] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.89%, 0.62%, 0.63%, and 0.54%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur content in each product is analyzed.
[0141] Example 8
[0142] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0143] S1: Take 1100g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 32%, and then add desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.38%.
[0144] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 300-mesh square-hole sieve to obtain coarse-grained and fine-grained desulfurized lithium slag. Among them, the fine-grained desulfurized lithium slag contains 98% -325 mesh.
[0145] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 28%, and then add 500g / t of oxalic acid, 200g / t of carboxymethyl cellulose, 150g / t of sodium fluorosilicate, and 120g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0146] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.5T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0147] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.0T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0148] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 10 min, the slurry concentration is 45%, and the fineness is -325 mesh, accounting for 96%.
[0149] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0150] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.87%, 0.61%, 0.65%, and 0.52%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0151] Example 9
[0152] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0153] S1: Take 1000g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.40%.
[0154] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 300-mesh square-hole sieve to obtain coarse-grained and fine-grained desulfurized lithium slag. Among them, the fine-grained desulfurized lithium slag contains 97% -325 mesh.
[0155] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 28%, and then add 600g / t of sodium hydroxide, 400g / t of water glass, 800g / t of sodium oleate and 200g / t of sodium dodecyl sulfonate as collectors for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0156] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.5T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0157] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.0T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0158] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 20 min, the slurry concentration is 40%, and the fineness is -325 mesh (98%).
[0159] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0160] S8: The above products are filtered and dried to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.78%, 0.52%, 0.56%, and 0.41%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0161] Example 10
[0162] A method for preparing low-alkali, high-purity silica-alumina micro powder from lithium slag, the process is as follows: Figure 1 As shown, specifically, it includes the following steps:
[0163] S1: Take 1000g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then carry out flotation operation in sequence with desulfurization flotation modifier, collector and frother to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.41%.
[0164] S2: The above-mentioned desulfurized lithium slag is classified using a hydrocyclone to obtain coarse-grained and fine-grained desulfurized lithium slag. Among them, the fine-grained desulfurized lithium slag contains 96% -325 mesh, and the coarse-grained desulfurized lithium slag contains 9% -325 mesh.
[0165] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 32%, and then add 600g / t of sodium hydroxide, 500g / t of sodium hexametaphosphate, 600g / t of sodium oleate and 200g / t of sodium dodecyl sulfonate as collectors for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0166] S4: The fine-grained lithium slag from step S2 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 2 and fine-grained silicon-aluminum powder.
[0167] S5: The low-alkali desulfurized lithium slag from step S3 was subjected to magnetic separation tests using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.2T) to obtain iron-rich slurry 1 and low-alkali silicon-aluminum powder. The iron-rich slurry 2 from step S4 and the iron-rich slurry 1 from step S5 were combined to obtain iron-rich slurry.
[0168] S6: The low-alkali silica-alumina powder from step S5 is ground using a ceramic ball mill to obtain low-alkali silica-alumina micro powder; the grinding time is 20 min, the slurry concentration is 40%, and the fineness is -325 mesh, accounting for 97%.
[0169] S7: Mix the fine-grained silicon-aluminum powder obtained in step S4 and the low-alkali silicon-aluminum powder obtained in step S6 to obtain a low-alkali, high-purity silicon-aluminum micro powder slurry.
[0170] S8: The above products are filtered and dried respectively to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.76%, 0.53%, 0.49%, and 0.32%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0171] Comparative Example 1
[0172] Based on the appendix Figure 2 This comparative example provides a traditional process for preparing silicon-aluminum micropowder from lithium slag. The specific steps are as follows:
[0173] S1: Take 1000g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then carry out flotation operations in sequence with desulfurization flotation modifier, collector and frother to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.40%.
[0174] S2: The desulfurized lithium slag from step S1 is subjected to iron removal treatment. Magnetic separation tests are conducted using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry and silicon-aluminum powder.
[0175] S3: The silica-alumina powder from step S2 is sieved and classified using a 325-mesh square-hole sieve to obtain coarse and fine silica-alumina powder. The coarse silica-alumina powder is then ground to obtain low-alkali silica-alumina micro powder. The grinding time is 20 minutes, the slurry concentration is 50%, and the fineness is -325 mesh (98%). Finally, the silica-alumina powder is combined together.
[0176] S4: The above products are filtered and dried to obtain gypsum powder, silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.87%, 0.64%, and 0.56%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0177] Comparative Example 2
[0178] Based on the appendix Figure 3 This comparative example provides a traditional process for preparing silicon-aluminum micropowder from lithium slag. The specific steps are as follows:
[0179] S1: Take 1000g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.40%.
[0180] S2: Add 500g / t of sodium hydroxide, 400g / t of water glass, 600g / t of sodium oleate and 200g / t of sodium dodecyl sulfonate as collectors to the desulfurized lithium slag in step S1 in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0181] S3: The low-alkali desulfurization lithium slag from step S2 is subjected to iron removal treatment. Magnetic separation tests are conducted using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry and silicon-aluminum powder.
[0182] S4: The silica-alumina powder from step S3 is sieved and classified using a 325-mesh square-hole sieve to obtain coarse and fine silica-alumina powder. The coarse silica-alumina powder is then ground to obtain low-alkali silica-alumina micro powder. The grinding time is 20 minutes, the slurry concentration is 50%, and the fineness is -325 mesh (98%). Finally, the silica-alumina powder is combined together.
[0183] S5: The above products are filtered and dried to obtain gypsum powder, silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.82%, 0.51%, and 0.43%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0184] Comparative Example 3
[0185] Based on the appendix Figure 4 This comparative example provides a traditional process for preparing silicon-aluminum micropowder from lithium slag. The specific steps are as follows:
[0186] S1: Take 1000g of lithium slag, the lithium slag contains 72% -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag, the SO3 content in the desulfurized lithium slag is 0.37%.
[0187] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 325-mesh square hole sieve to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag.
[0188] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 800g / t of sulfuric acid, 300g / t of carboxymethyl cellulose, 100g / t of sodium fluorosilicate, and 200g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0189] S4: The low-alkali desulfurized lithium slag from step S3 is ground using a ceramic ball mill to obtain low-alkali desulfurized micro powder; the grinding time is 20 minutes, the slurry concentration is 50%, and the fineness is -325 mesh (98%).
[0190] S5: Combine the fine-grained desulfurized lithium slag from step S2 and the low-alkali desulfurized lithium slag from step S4 together for magnetic separation. Magnetic separation tests are conducted using a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to obtain iron-rich slurry and low-alkali high-purity silicon-aluminum slurry.
[0191] S6: The above products are filtered and dried respectively to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.96%, 0.68%, 0.62%, and 0.54%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0192] Comparative Example 4
[0193] Based on the appendix Figure 5 This comparative example provides a traditional process for preparing silicon-aluminum micropowder from lithium slag. The specific steps are as follows:
[0194] S1: Take 1000g of lithium slag, with 70% of the lithium slag containing -200 mesh, add it to a 3L flotation cell, add water to adjust the slurry concentration to 30%, and then add the desulfurization flotation modifier, collector and frother in sequence to carry out flotation operation to obtain gypsum slag and desulfurized lithium slag. The SO3 content in the desulfurized lithium slag is 0.37%.
[0195] S2: The above-mentioned desulfurized lithium slag is screened and classified using a 325-mesh square hole sieve to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag.
[0196] S3: Place the coarse-grained desulfurized lithium slag from step S2 into a 1L flotation cell, add water to adjust the pulp concentration to 30%, and then add 800g / t of sulfuric acid, 600g / t of water glass, 200g / t of sodium fluorosilicate, and 100g / t of dodecylamine in sequence for flotation to obtain alkali-rich slag and low-alkali desulfurized lithium slag.
[0197] S4: Combine the fine-grained desulfurized lithium slag from step S2 and the low-alkali desulfurized lithium slag from step S3 into one magnetic separation test. Use a weak magnetic separator (magnetic field strength 0.4T) and a high gradient strength separator (magnetic field strength 1.5T) to conduct magnetic separation tests to obtain iron-rich slurry and low-alkali high-purity silicon-aluminum slurry.
[0198] S5: The low-alkali high-purity silicon-aluminum slurry from step S4 is classified and ground to obtain a low-alkali high-purity silicon-aluminum micro powder slurry; the grinding time is 20 min, the slurry concentration is 50%, and the fineness is -325 mesh, accounting for 98%.
[0199] S6: The above products are filtered and dried respectively to obtain gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of the gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material are 0.75%, 0.42%, 0.46%, and 0.63%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur in each product are tested and analyzed.
[0200] Comparative Example 5
[0201] The process is consistent with that of Example 1 of this invention. In step S2, the desulfurized lithium slag is sieved and classified using a 200-mesh square-hole sieve to obtain coarse-grained and fine-grained desulfurized lithium slag. The fine-grained desulfurized lithium slag contains 82% -325 mesh material. The final products are gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder, and iron-rich material. The moisture contents of these products are 0.76%, 0.51%, 0.46%, and 0.42%, respectively. The mass of each product is weighed, the yield of each product is calculated, and the potassium, sodium, iron, lithium, and sulfur content in each product is analyzed.
[0202] Comparative Example 6
[0203] Using the same acid-clinked raw material as the lithium slag upstream of the present invention, and following the process of Example 1 in patent CN 118792502 A, gypsum powder, silica-alumina micro powder and iron-rich material were prepared. The product yield was calculated by weighing each product, and the potassium, sodium, iron, lithium and sulfur content in each product was detected and analyzed.
[0204] Performance testing:
[0205] Based on the lithium measurement method in GB / T 17413.1-2010 "Chemical Analysis Methods for Lithium, Rubidium and Cesium Ores", the lithium content (calculated as Li2O) in gypsum powder, feldspar concentrate, low-alkali high-purity silica-alumina micro powder and iron-rich material obtained in Examples 1-10 and Comparative Examples 1-6 was determined.
[0206] The SO3 content in each product of Examples 1-10 and Comparative Examples 1-4 was determined based on GB / T 5484-2012 "Methods for Chemical Analysis of Gypsum".
[0207] The contents of K2O, Na2O, and Fe2O3 in the products of Examples 1-10 and Comparative Examples 1-4 were determined based on GB / T 14506.31-2019 "Chemical Analysis Methods for Silicate Rocks Part 31: Determination of 12 Components including Silicon Dioxide by Lithium Metaborate Fusion-Inductively Coupled Plasma Atomic Emission Spectrometry".
[0208] The test results of the content of silicon-aluminum micro powder products in Examples 1-10 and Comparative Examples 1-6 are statistically shown in Table 2.
[0209] Table 2
[0210]
[0211] The test results of the gypsum powder product index content of Examples 1-10 and Comparative Examples 1-6 are statistically shown in Table 3.
[0212] Table 3
[0213]
[0214] The test results of the feldspar concentrate product index content of Examples 1-10 and Comparative Examples 1-6 are statistically shown in Table 4.
[0215] Table 4
[0216]
[0217] The test results of the iron-rich material product index content of Examples 1-10 and Comparative Examples 1-6 are statistically shown in Table 5.
[0218] Table 5
[0219]
[0220] As shown in Tables 2-5, the sodium and potassium content in the low-alkali, high-purity silicon-aluminum micropowders obtained in Experiments 1-10 of Table 2 is significantly better than that in Comparative Examples 1-2. Without classification and potassium / sodium removal treatment, the K₂O + Na₂O content in the silicon-aluminum micropowder is as high as 1.22%; when potassium / sodium removal treatment is performed directly without classification, the K₂O + Na₂O content in the obtained silicon-aluminum micropowder is as high as 0.71%, which also fails to meet the required standards. Comparative Example 3 shows that although the silicon-aluminum micropowder meets the required standards, the high Fe₂O₃ content in the product will also affect its market application. Comparative Example 4 shows that the process flow has a smaller impact on the product standards, but the yield of silicon-aluminum micropowder is reduced. This indicates that classification treatment is more beneficial for obtaining low-alkali, high-purity silicon-aluminum micropowder. Comparative Example 5 shows that when the desulfurized lithium slag is screened and graded using a 200-mesh square-hole sieve, the yield of silicon-aluminum micropowder is improved, but the potassium and sodium content in the product is also significantly increased, with K2O+Na2O reaching 0.83%, which is not conducive to the preparation of low-alkali, high-purity silicon-aluminum micropowder. Therefore, the particle size control requirements are relatively high during screening and grading. Comparative Example 6 shows that using the same potassium- and sodium-rich lithium slag raw material as in the embodiments of this invention, the yield of silicon-aluminum micropowder prepared according to the process of patent CN 118792502A is higher than that of this invention, but at the same time, the K2O+Na2O content in the product is 0.73%, which is significantly higher than that of this invention.
[0221] As shown in Table 3, the yield and quality of gypsum powder products in Examples 1-10 and Comparative Examples 1-5 were less affected, mainly because the desulfurization methods were the same in each process, resulting in relatively stable indicators. However, in Comparative Example 6, the yield of gypsum powder decreased, while the SO3 content in the product increased, indicating that the process in Comparative Example 6 was more likely to produce high-grade gypsum powder products.
[0222] As shown in Table 4, without classification, the yield of feldspar concentrate obtained by directly removing potassium and sodium increased, while the K2O+Na2O content in the concentrate decreased, thus affecting the yield of silica-alumina powder and the alkali metal content.
[0223] As shown in Table 5, the yields of the examples ranged from 11.36% to 11.64%, generally low with minimal fluctuations. The yields of the comparative examples were significantly higher, ranging from 11.30% to 17.82%, with Comparative Example 1 reaching a high of 17.82%, far exceeding that of the examples. The Li₂O grades of the examples ranged from 2.01% to 2.23%, generally high and stable. The Li₂O grades of the comparative examples were relatively low, especially Comparative Example 6 at only 0.66%, while the others ranged from 1.22% to 1.78%.
Claims
1. A method for preparing low-alkali, high-purity silicon-aluminum micropowder from lithium slag, wherein the lithium slag is a solid waste residue obtained after lithium extraction from lithium-containing minerals via acid extraction, neutralization, and filtration, characterized in that... The method includes the following steps: a. Desulfurization: Lithium slag is pulped and desulfurized to obtain gypsum slag and desulfurized lithium slag. The gypsum slag is dehydrated to obtain gypsum powder. b. Grading: The desulfurized lithium slag from step a is graded to obtain coarse-grained desulfurized lithium slag and fine-grained desulfurized lithium slag. The coarse-grained desulfurized lithium slag contains less than 10% -325 mesh, and the fine-grained desulfurized lithium slag contains more than 95% -325 mesh. c. Removal of potassium, sodium and iron: The coarse-grained desulfurized lithium slag from step b is subjected to potassium and sodium removal treatment to obtain alkali-rich slag and low-alkali desulfurized lithium slag. The low-alkali desulfurized lithium slag is then subjected to iron removal treatment to obtain low-alkali silica-alumina powder and iron-rich slurry 1. The alkali-rich slag is dewatered to obtain feldspar concentrate. The fine-grained desulfurized lithium slag from step b is subjected to iron removal treatment to obtain iron-rich slurry 2 and fine-grained silica-alumina powder. Iron-rich slurry 1 and iron-rich slurry 2 are combined to obtain iron-rich slurry. The iron-rich slurry is dewatered to obtain iron-rich material. d. Grinding and mixing: Grind the low-alkali silicon-aluminum powder from step c to obtain low-alkali silicon-aluminum micro powder. Then mix the low-alkali silicon-aluminum micro powder with the fine-particle silicon-aluminum powder from step c, and dehydrate to obtain low-alkali high-purity silicon-aluminum micro powder. Alternatively, the low-alkali silicon-aluminum powder from step c can be mixed with fine-grained silicon-aluminum powder, ground, and then dehydrated to obtain low-alkali, high-purity silicon-aluminum micro powder.
2. The method according to claim 1, characterized in that, In step a, the lithium slag particle size is -200 mesh, accounting for 50-80 wt%; the slurry mass concentration is preferably 20-50%; and the desulfurization treatment preferably includes at least one of flotation and acid dissolution.
3. The method according to claim 1, characterized in that, The gypsum powder obtained in step a contains SO3 ≥ 42%, while the desulfurized lithium slag contains SO3 ≤ 0.5%.
4. The method according to claim 1, characterized in that, In step b, the grading process includes at least one of screening grading, hydrocyclone grading, and spiral grading.
5. The method according to claim 1, characterized in that, In step c, the removal of potassium and sodium is carried out by flotation. The flotation for removing potassium and sodium includes at least one of a modifier, a depressant, an activator, and a collector. The dosage of the modifier is 500–2000 g / t, the dosage of the depressant is 100–1000 g / t, the dosage of the activator is 50–300 g / t, and the dosage of the collector is 100–1000 g / t. The modifier for removing potassium and sodium includes at least one of sulfuric acid, sodium hydroxide, sodium carbonate, and oxalic acid. The depressant includes at least one of water glass, sodium silicate, sodium hexametaphosphate, starch, carboxymethyl cellulose, and citric acid. The activator includes at least one of sodium fluorosilicate, sodium fluoride, sodium dodecyl sulfate, ammonium dodecyl sulfate, ethylenediamine phosphate, and sodium diethylamine phosphate. The collector includes at least one of dodecylamine, oleic acid, sodium oleate, sodium dodecyl sulfonate, sodium petroleum sulfonate, octyl hydroxamic acid, and dodecyl trimethylammonium chloride. The removal of iron preferably includes at least one of magnetic separation or gravity separation.
6. The method according to claim 1, characterized in that, In step c, the feldspar concentrate contains Na2O+K2O≥9.0%, and the low-alkali desulfurized lithium slag contains Na2O+K2O≤0.5%.
7. The method according to claim 1, characterized in that, In step c, the Fe2O3 content in the fine-grained silica-alumina powder is ≤0.4%, the Fe2O3 content in the low-alkali silica-alumina powder is ≤0.4%, and the Fe2O3 content in the iron-rich material is ≥4.0%.
8. The method according to claim 1, characterized in that, In step d, the fineness of the obtained low-alkali silica-alumina micro powder is -325 mesh with a content ≥95%.
9. The method according to claim 1, characterized in that, In step d, the grinding process includes at least one of ball milling and rod milling; the grinding time is preferably 10-30 min, and the slurry concentration is preferably 40-60%. The grinding process is preferably performed using a ceramic ball mill.
10. The method according to claim 1, characterized in that, The dehydration process includes at least one of concentration, filtration, and drying. Preferably, the dehydration process results in a product moisture content of ≤2.0%, more preferably 1.0%.
11. The method according to any one of claims 1 to 10, characterized in that, The obtained low-alkali, high-purity silicon-aluminum micro powder contains Na2O+ K2O < 0.50%, Li2O ≤ 0.2%, SO3 < 0.40%, and Fe2O3 < 0.40%; preferably, Na2O+ K2O < 0.40%.
12. The method according to claim 1, characterized in that, The lithium slag contains 50%–65% SiO2, 15%–25% Al2O3, 3%–8% SO3, 0.3%–1.5% K2O, 0.2%–1.0% Na2O, 0.8%–1.5% Fe2O3, and 0.2%–0.5% Li2O.
13. The method according to claim 1, characterized in that, The gypsum powder is used to prepare gypsum board, gypsum blocks or cement retarder; the feldspar concentrate is used as a ceramic raw material; the low-alkali high-purity silica-alumina micro powder is used to replace pyrophyllite in the preparation of alkali-free glass fiber; the iron-rich material is also used for further sorting to obtain at least one of lithium concentrate, iron material, tantalum-niobium concentrate or tin concentrate.
14. Low-alkali, high-purity silica-alumina micro powder, characterized in that, It is prepared by the method described in any one of claims 1 to 13.
Citation Information
Patent Citations
Method for extracting lithium from spodumene and simultaneously recovering low-iron and low-sulfur silicon-aluminum micropowder, high-purity gypsum, tantalum-niobium concentrate and lithium-rich iron material
CN117165787B
Method for removing potassium and sodium in lithium slag
CN119638237A
Method for extracting potassium, sodium, rubidium and cesium in lithium slag
CN119876610A